2020
DOI: 10.3390/foods9050666
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Dehydration Levels on Volatile Profiles, Phenolic Contents and Skin Hardness of Alkaline Pre-Treated Grapes cv Muscat of Alexandria (Vitis vinifera L.)

Abstract: A dehydration experiment was carried out on Vitis vinifera L. cv Muscat of Alexandria (synonym Zibibbo) following the process for the production of renowned special dessert wines produced on Pantelleria island (Sicily, Italy). Harvested berries were pre-treated in a sodium hydroxide dipping solution (45 g/L, dipped for 185 s, 25 °C) to accelerate the drying process, rinsed, and dehydrated in simulated conditions (relative humidity 30%, 30 °C temperature, air speed 0.9 m/s). Three dehydration levels were achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…Peak 15 (54.89 min; Figure 2) was the next abundant monoterpenediol, with a higher absorbance at 190, 205 and 282 nm (Figure 3O). Several researchers have pointed out that the most abundant monoterpenediols in Muscat of Alexandria grapes are 8-hydroxylinalool, 2,6-dimethyl-3,7-octadiene-2,6-diol, 3,7dimethyl-1,5-octadiene-3,7-diol, 3,7-dimethyl-1,7-octadiene-3,6-diol, 8-hydroxynerol and 8-hydroxygeraniol [16,[35][36][37]. Therefore, it could be associated with aglycone of the more important monoterpenediols identified above.…”
Section: Monoterpenediol Glycosidesmentioning
confidence: 99%
“…Peak 15 (54.89 min; Figure 2) was the next abundant monoterpenediol, with a higher absorbance at 190, 205 and 282 nm (Figure 3O). Several researchers have pointed out that the most abundant monoterpenediols in Muscat of Alexandria grapes are 8-hydroxylinalool, 2,6-dimethyl-3,7-octadiene-2,6-diol, 3,7dimethyl-1,5-octadiene-3,7-diol, 3,7-dimethyl-1,7-octadiene-3,6-diol, 8-hydroxynerol and 8-hydroxygeraniol [16,[35][36][37]. Therefore, it could be associated with aglycone of the more important monoterpenediols identified above.…”
Section: Monoterpenediol Glycosidesmentioning
confidence: 99%
“…The free and glycosylated varietal aroma compounds were extracted from three replicates of 50 fresh grape berries, which were processed following the procedure described by Fracassetti et al (2017) and Corona et al (2020). The berries were de-seeded and the pulp was separated from the skin by adding Na2S2O5 (100 mg).…”
Section: Agronomic Traits and Grape Chemical Compositionmentioning
confidence: 99%
“…The GC-MS conditions which were used are reported by Corona et al (2020). The detection was carried out by electron impact mass spectrometry in total ion current (TIC) mode using an ionisation energy of 70 eV.…”
Section: Agronomic Traits and Grape Chemical Compositionmentioning
confidence: 99%
“…The accumulation of desirable key metabolites during postharvest dehydration is inhibited by rapid dehydration conditions that shorten the berry lifetime. Metabolomics and transcriptomics have demonstrated that the dehydration process results in modulation of the expression of various genes implicated in grape metabolism, such as secondary metabolism of phenols, terpenes, and lipids [10]. The water loss is reflected in the cell metabolism that transitions from aerobic to anaerobic [18,29].…”
Section: Free Volatile Aroma Compounds In Fresh and Dehydrated Grapesmentioning
confidence: 99%
“…Chamber-drying techniques in controlled conditions as an alternative to traditional sun drying revealed a significant impact of the dehydration rate and temperature on the modification of volatile compounds from the grapes [4][5][6]. Grape dehydration causes substantial water loss and a gradual increase in sugar concentration, which promotes the synthesis of metabolites that lead to the formation of the typical flavor of the sweet wines [4,[7][8][9][10]. Therefore, grape dehydration is one of the most important steps in the production of naturally sweet wine Prošek that influences the production of key volatile compounds in the grape variety used.…”
Section: Introductionmentioning
confidence: 99%